Plastid Phylogenomics and Plastome Evolution of Nandinoideae (Berberidaceae) - Song, Shiqiang; Zubov, Dmitriy; Comes, Hans Peter; Li, Haiwen; Liu, Xuelian; Zhong, Xin; Lee, Joongku; Yang, Zhaoping; Li, Pan (Frontiers in Plant Science, 2022)
Subfamily Nandinoideae Heintze (Berberidaceae), comprising four genera and ca. 19 species, is disjunctively distributed in eastern North America vs. Eurasia (eastern Asia, Central Asia, Middle East and southeastern Europe), and represents an ideal taxon to explore plastid phylogenomics and plastome evolution in Berberidaceae. In this study, we sequenced and assembled 20 complete plastomes, representing three genera and 13 species of Nandinoideae. Together with six plastomes from GenBank, a total of 26 plastomes, representing all four genera and 16 species of Nandinoideae, were used for comparative genomic and phylogenomic analyses. These plastomes showed significant differences in overall size (156,626–161,406 bp), which is mainly due to the expansion in inverted repeat (IR) regions and/or insertion/deletion (indel) events in intergenic spacer (IGS) regions. A 75-bp deletion in the ndhF gene occurred in Leontice and Gymnospermium when compared with Nandina and Caulophyllum. We found a severe truncation at the 5’ end of ycf1 in three G. altaicum plastomes, and a premature termination of ropC1 in G. microrrhynchum. Our phylogenomic results support the topology of (Nandina, (Caulophyllum, (Leontice, Gymnospermium))). Within the core genus Gymnospermium, we identified G. microrrhynchum from northeastern Asia (Clade A) as the earliest diverging species, followed by G. kiangnanense from eastern China (Clade B), while the rest species clustered into the two sister clades (C and D). Clade C included three species from West Tianshan (G. albertii, G. darwasicum, G. vitellinum). Clade D consisted of G. altaicum from northern Central Asia, plus one species from the Caucasus Mountains (G. smirnovii) and three from southeastern Europe (G. odessanum, G. peloponnesiacum, G. scipetarum). Overall, we identified 21 highly variable plastome regions, including two coding genes (rpl22, ycf1) and 19 intergenic spacer (IGS) regions, all with nucleotide diversity (Pi) values > 0.02. These molecular markers should serve as powerful tools (including DNA barcodes) for future phylogenetic, phylogeographic and/or conservation genetic studies on those rare, endangered species.